Evidence of Rapid Modulation by Social Information of Subjective, Physiological, and Neural Responses to Emotional Expressions - Mermillod, Martial; Grynberg, Delphine; Pio-Lopez, Léo; Rychlowska, Magdalena; Beffara, Brice; Harquel, Sylvain; Vermeulen, Nicolas; Niedenthal, Paula M.; Dutheil, Frédéric; Droit-Volet, Sylvie (Frontiers in Behavioral Neuroscience, 2018)
Recent research suggests that conceptual or emotional factors could influence the perceptual processing of stimuli. In this article, we aimed to evaluate the effect of social information (positive, negative or no information related to the character of the target) on subjective (perceived and felt valence and arousal), physiological (facial mimicry) as well as on neural (P100 and N170) responses to dynamic emotional facial expressions (EFE) that varied from neutral to one of the six basic emotions. Across three studies, the results showed (1) reduced ratings of valence and arousal of EFE associated with incongruent social information (Study 1), (2) increased electromyographical responses (Study 2) and (3) significant modulation of P100 and N170 components (Study 3) when EFE were associated with social (positive and negative) information (vs. no information). These studies revealed that positive or negative social information reduces subjective responses to incongruent EFE and produces a similar neural and physiological boost of the early perceptual processing of EFE irrespective of their congruency. In conclusion, the article suggests that the presence of positive or negative social context modulates early physiological and neural activity preceding subsequent behavior.